Endoscopic submucosal dissection for rectal neoplasia extending to the dentate line: European experience - Probst, Andreas; Ebigbo, Alanna; Märkl, Bruno; Ting, Saskia; Schaller, Tina; Anthuber, Matthias; Fleischmann, Carola; Messmann, Helmut (Endoscopy International Open, 2018)
Background and study aims The ideal treatment strategy for rectal neoplasia extending to the dentate line (RNDL) is not well defined. Endoscopic mucosal resection (EMR) and submucosal dissection (ESD) compete with surgical techniques such as transanal endoscopic microsurgery (TEM). Non-Asian data and prospective data on ESD are lacking. The study aim was to evaluate the role of ESD in treatment of RNDL in a Western center.Patients and methods Eighty-six patients with rectal adenomas were included. ESD was performed in 86 rectal adenomas including 24 RNDLs (27.9 %) and 62 lesions distant from the dentate line (72.1 %).Results En bloc resection rate was comparable (91.7 % vs. 93.5 %, P = 0.670) between ESD for RNDL and non-RNDL. R0 resection rate was significantly lower in ESD for RNDL compared to that for non-RNDL (70.8 % vs 88.7 %; P = 0.039), but most non-R0 resection was unclear margin (Rx) and was not obvious positive margin (R1). Accordingly, the recurrence rate after ESD for RNDL (4.5 %) was not statistically different from that for non-RNDL (0 %, P = 0.275) and was lower than that previously reported for EMR. Median procedure time was 127 vs. 110 minutes (P = 0.182). Risk of delayed bleeding (20.8 % vs. 0 %, P = 0.001) and postinterventional pain (33.3 % vs. 14.5 %, P = 0.07) increased in RNDL cases, but they were managed conservatively. Incidence of stricture (4.2 % vs. 1.6 %, P = 0.483) and perforation (0 % vs. 1.6 %, P = 1.000) were similar.Conclusions ESD is a feasible and safe resection technique for RNDLs. A randomized controlled trial comparing ESD to other methods (EMR or transanal surgery) is warranted.